How do principals of English-medium primary schools understand Māori students achieving educational success as Māori, and what are the factors that influence the development of this understanding : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University, Manawatū, New Zealand - De Goldi, John Anthony (Massey University, 2018)
This thesis investigates how the principals of English-medium primary schools understand Māori students achieving educational success as Māori. Additionally, it explores the factors that support and hinder the development of their understanding. A qualitative case-study was used to explore the understanding and experiences of the 28 principals of all English-medium, full and contributing primary schools on Te Tai Poutini West Coast of Te Wai Pounamu South Island. Twenty-seven principals were interviewed in their own schools over a period of two months, while one principal completed an on-line questionnaire. The study found that English-medium primary school principals’ understanding of Māori students achieving educational success as Māori align largely with the vision for young people who are confident, connected, actively engaged lifelong learners. Additionally, principals incorporate the acquisition of other skills and knowledge including the learning of te reo Māori that will enable students to participate in and contribute to te ao Māori. Although their descriptions approximate the broad student outcomes outlined in Ka Hikitia, few principals in this study refer specifically to them. The findings from this study also bring to light a complex lattice of interacting connections and disconnections with place, people, and the power of Pākehā/Eurocentric hegemony that frames and influences the development of principals understanding of Māori students’ educational success as Māori. Factors of physical and cultural isolation, and disconnection with Poutini Ngāi Tahu, hinder principals’ ability to develop a wider understanding of Māori students’ educational success as Māori. The thesis concludes that although principals are the leaders of learning and teaching in their schools, they need support from, whānau, hapū, iwi and perhaps most importantly, the Ministry of Education, to connect with people, place, and the power of Pākehā/Eurocentric hegemony in order to develop their understanding of Māori students achieving success as Māori.
Keywords: Elementary school principals; Maori (New Zealand people); Maori children; Success in children; Tumuaki; Kura tuatahi; Tamariki; Mātauranga